2021
DOI: 10.3390/w13091179
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Chlorophyll-a Concentration in Donghu Lake Based on Machine Learning Algorithm

Abstract: Machine learning algorithm, as an important method for numerical modeling, has been widely used for chlorophyll-a concentration inversion modeling. In this work, a variety of models were built by applying five kinds of datasets and adopting back propagation neural network (BPNN), extreme learning machine (ELM), support vector machine (SVM). The results revealed that modeling with multi-factor datasets has the possibility to improve the accuracy of inversion model, and seven band combinations are better than se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In this paper, taking the experimental sample area of Nanyi Lake as an example, a sampling design study was carried out on the three parameters of Chl-a, TSM, and SD. Previous studies have shown that the near-infrared/red, red/green, and green bands can be used as remote sensing feature bands for Chl-a, TSM, and SD [43][44][45][46][47]. Therefore, this paper uses Band 8/Band 3, Band 4/Band 3, and Band 3 of Sentinel-2 satellites as the sensitive bands of Chl-a, TSM, and SD and generates the spatial distribution characteristics map of the water parameters.…”
Section: Spatial Distribution Of Water Parametersmentioning
confidence: 99%
“…In this paper, taking the experimental sample area of Nanyi Lake as an example, a sampling design study was carried out on the three parameters of Chl-a, TSM, and SD. Previous studies have shown that the near-infrared/red, red/green, and green bands can be used as remote sensing feature bands for Chl-a, TSM, and SD [43][44][45][46][47]. Therefore, this paper uses Band 8/Band 3, Band 4/Band 3, and Band 3 of Sentinel-2 satellites as the sensitive bands of Chl-a, TSM, and SD and generates the spatial distribution characteristics map of the water parameters.…”
Section: Spatial Distribution Of Water Parametersmentioning
confidence: 99%
“…Mohammad M. Hasan et al have adjusted the hyperparameters for unmanned aerial vehicle target classification using range/micro-Doppler features combined with R-PCA-SVM, ultimately achieving a high accuracy of 98% [30]. Tang et al achieved improved accuracy in inverting chlorophyll a concentration in Donghu through multi-factor modeling using various machine learning methods, showcasing the potential for advancement in this field [31]. Xu et al have showcased enhanced accuracy when employing Bayesian methods in the crop radiative transfer model inversion process [32].…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al established the inversion model of Chl-a concentrations with synchronous image data of Taihu Lake by using an RBF neural network model [42]. Tang et al used a variety of band combinations as the input of an SVM model to retrieve Chl-a concentrations [43,44]. Feng et al used convolutional neural networks for water quality inversion and achieved high inversion accuracy [45].…”
Section: Introductionmentioning
confidence: 99%